The Principles of Law to Resolve Disharmony of Regulations in the Calculation of Financial Loss to the State - Ronald Hasudungan Sianturi (Proceedings of AICS - Social Sciences, 2016)
Upholding the rule of law remains a serious challenge in Indonesia, that law enforcement should be carried out based on the principle of legality, included in the calculation of financial loss to the state in law enforcement against corruption. Certainty calculation of losses to the state is difficult to be achieved because of disharmony some regulations in the definition, the process and subjectivity in determining the method of calculation of losses to the state. Conflicts of some regulations makes law enforcement became ineffective, inefficient and inconsistent. This research aims to investigate the principles of law in the calculation of financial loss to the state to overcome conflicting regulations. This research is juridical normative. The data used are related regulations and court verdicts. This research use statue approach and conceptual approach. This research found that disharmony of regulations in the calculation of financial loss to the state can be solved with lex superiori derogat legi inferiori and lex specialis derogat legi generali.